The Relationship Between Dental and Oral Health Knowledge and Gingiva Status of Pregnant Women - Mery Efiani; Desih Welliam; Asmawati, Asmawati; Stevani Vauziah Alzahra Hamsa (Sean Institute, 2025)
Oral health encompasses not only teeth but also gums, periodontal tissues, and soft tissues of the cheeks, tongue, and lips. Pregnant women have general knowledge about periodontal disease, but little understanding of its causes. Gum disease during pregnancy can lead to premature birth and low birth weight babies, the purpose of this study was to determine the relationship between pregnant women's knowledge of oral health and gingival status. The research used was observational analytic with a cross-sectional design, naely research conducted at the same time to connect between variables . inflammation. This study obtained a significant value of the normality test for the knowledge questionnaire of 0.05, namely 0.163, and gingival status of 0.05, namely 0.234. Based on the test of the relationship between knowledge about dental and oral health and gingival status in pregnant women, the p-value was 0.000 ≤( 0.05).There is a relationship between knowledge about dental and oral health and gingival status in pregnant women.